Teachers’ perceptions of the organisational climate: a tool for promoting instructional improvement - Aldridge, Jill; Fraser, B. (Carfax, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group The current push for principals’ to be accountable for student outcomes has led to a renewed interest in the role of leadership in instructional improvement. This article describes the development and validation of a survey that focused on organisational management features that are likely to bring about improvement in instruction. The development of the instrument involved a multistage approach that included: identifying key organisational management features important to instructional leadership and an effective school, based on research and theoretical underpinnings; clearly articulating key constructs; and modifying, adapting and developing items to assess those constructs. After pilot testing the survey, the survey was administered to 216 teachers selected from four high schools in Western Australia. To ensure that the survey was reliable, we used [Trochim W. M. and J. P. Donnelly. 2006. The Research Methods Knowledge Base. 3rd ed. Cincinnati, OH: Atomic Dog] framework for construct validity. Analysis of the data provided evidence to support the reliability and validity of the questionnaire in terms of both the translation and criterion validity. The development of this survey provides principals with an economical and psychometrically sound tool that can be used as part of a process involving critical self-reflection.